The role of design in product-service organisations - Beltagui, Ahmad (2011)
Amid claims that we live in a service economy, the distinction between manufacturing and services is blurred. Many manufacturers have made a product-service transition, whereby services are integrated with products, to meet demand for access to the benefits, but not the risks of ownership of products. Many aspects of this transition and the product-service offerings which result require investigation, principally the relationship with design. Design itself is a concept open to many interpretations and studies of it have been hampered by the lack of an accepted theoretical framework.